PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada PT Telekomunikasi Indonesia Unit Bagian Witel Semarang) - Jeany, Sherly Vilianti; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research is to explain how the variable of job satisfaction, organizational commitment, and organizational culture influence to PT Telekomunikasi Indonesia Witel Unit in Semarang employee performance. Data collection was done by questionnaire.The sample used in this research were employees of PT Telekomunikasi Indonesia Witel Unit in Semarang 80 people in total. The sampling technique was conducted using Simple Random Sampling. Mechanical testing of the data used in this research include the instrument test (validity and reliability test), classical assumption test (normality test, multicoloniarity, and heteroscedasticity test), multiple linear regression analysis, t test, F test, and coefficient of determination test (R2) using SPSS application.The result of this research shows that job satisfaction, organizational commitment, and organizational culture influence positively and significantly to the employee performance. Variable used in this research give positive response, meaning the job satisfaction, organizational commitment, and organizational culture improving the performance of PT Telekomunikasi Indonesia Witel Unit in Semarang employee. Value of determination coefficient or R2 is 0,517, which means employee performance is affected by job satisfaction, organizational commitment, and organizational culture amounted to 51,7%.